Ustekinumab in the Treatment of Crohn’s Disease—A Narrative Review on Clinical Efficacy and Safety Profile - Dawid Piecuch; Edyta Hańczyk; Szymon Kopciał; Natalia Pawelec; Weronika Mazur; Karolina Kornatowska (Pharmacy, 2025)
Crohn’s disease (CD) is a chronic inflammatory disorder of the gastrointestinal tract that leads to significant deterioration in patients’ quality of life. Biologic therapy, including the use of ustekinumab (UST), is a modern approach to treating the moderate to severe form of CD, especially in patients refractory to traditional treatments. UST, which acts as an interleukin IL-12 and IL-23 antagonist, has shown high efficacy in reducing inflammation, improving quality of life, and promoting mucosal regeneration and fistula healing. However, the use of biologic therapies, such as UST, has challenges related to the timing of treatment and patient response, including the problem of immunogenicity. To determine the clinical efficacy and safety profile of UST in the treatment of CD, a review of the literature published in the PubMed database over the last 5 years was conducted. After excluding articles that did not meet the inclusion criteria, we analyzed 42 clinical studies. The review discusses the available data on the efficacy and safety of UST, as well as its comparison with other biologic therapies, such as infliximab and adalimumab. UST, although not significantly greater to adalimumab, has lower immunogenicity and higher treatment retention. The therapeutic value of UST is also confirmed by biosimilars such as ABP 65 and FYB202, which show comparable efficacy and safety profile. The analysis of predictive biomarkers, such as serum drug levels and baseline eosinophil levels, could be an important element in the future personalization of CD treatment. The review’s findings point to the importance of further research to improve the tailoring of therapies to individual patients and improve long-term treatment outcomes.